The Dynamics of Nitrate Reductase in Tea Leaves - M. Husian Kasim, Taryono, Sriyanto Waluyo,; Hari Kartiko (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2013)
ABSTRACTCrop productivity depends on adequate nitrogen supply. Nitrate is one form of nitrogen in the soil which is absorbed by plant root and the process of nitrate reduction in plant cells was catalyzed by nitrate reductase, therefore NRA might be able to be used as biochemical tools to estimate tea leaves productivity and the dynamics of NRA can be used to check the nitrogen availability in the soil.To study the dynamic of nitrate reductase in respond to fertilizer application, an experiment which includes two factors i.e. plant materials and nitrogen fertilizer application was conducted during rainy season at experimental field of Pagilaran tea plantation. Factorial treatment design with plant materials i.e. 2 vegetative origin of TRI-2024 and TRI-2025 and 1 seed origin were used as first factor, while 2 dosages of nitrogen fertilization (0 and 250 kg/ha urea + 60 kg/ha SP36 + 60 kg/ha KCl) used as the second factor with 3 replications. The activity of nitrate reductase was then measured every week continuously started 8 weeks before fertilizer application (WBF) and ended 8 weeks after fertilizer application (WAF).There result showed that the dynamics of NRA was depend on soil moisture and nitrate availability in the soil. When urea was used as nitrogen source, urea will be hydrolyzed first to produce ammonium and then ammonium will be nitrified to nitrate. This process could be studied from NRA in tea leaves, though NRA seemed could not be used as biochemical tool to estimate tea leaves productivity.Keyword : Nitrat reductase, tea, production